The m6A-ncRNAs axis in diabetes complications: novel mechanism and therapeutic potential - Yu, Siming; Li, Chunsheng; Lu, Xinxin; Han, Zehui; Li, Yue; Yuan, Xingxing; Guo, Dandan (Frontiers in Endocrinology, 2024)
Diabetes, a multifaceted metabolic disorder, poses a significant global health burden with its increasing prevalence and associated complications, such as diabetic nephropathy, diabetic retinopathy, diabetic cardiomyopathy, and diabetic angiopathy. Recent studies have highlighted the intricate interplay between N 6 -methyladenosine (m 6 A) and non-coding RNAs (ncRNAs) in key pathways implicated in these diabetes complications, like cell apoptosis, oxidative stress, and inflammation. Thus, understanding the mechanistic insights into how m 6 A dysregulation impacts the expression and function of ncRNAs opens new avenues for therapeutic interventions targeting the m 6 A-ncRNAs axis in diabetes complications. This review explores the regulatory roles of m 6 A modifications and ncRNAs, and stresses the role of the m 6 A-ncRNA axis in diabetes complications, providing a therapeutic potential for these diseases.